The role of information technology in the future of 3D biofabrication. Issue 1 (January 2017) - Andréa Dernowsek, Janaina de; Rezende, Rodrigo Alvarenga; Lopes da Silva, Jorge Vicente
Information technology (IT) is ubiquitous in recent human existence. The aim of this article is to present some basic concepts and specific demands that biofabrication may place on IT. Some of these technologies are already available, with a need for improvement, while others will need to be newly developed. Technologies that clearly, precisely and unambiguously specify a tissue or organ are unavailable. A move from expensive in vitro and in vivo assays toward in silico technologies will allow for exhaustive tests and optimization of human substitutes by means of computer biological systems. To complete this substitution, biofabrication lines shall be established; integrating what was planned and designed into physical processes executed by automatic machines. Biofabrication will impose great challenges, since many tools will need to be developed by engineers together with biologists. Many other concerns and challenges will be faced in the path to an autonomous biofabrication line, including cybernetic and biological safety issues. Therefore, the main aim of this paper is to shed some light and establish a primary nexus between the present and future applications of IT in biofabrication.